1997
DOI: 10.1152/jappl.1997.83.4.1276
|View full text |Cite
|
Sign up to set email alerts
|

Passive sensitization of human airways induces myogenic contractile responses in vitro

Abstract: We assessed effects of passive sensitization on human bronchial smooth muscle (BSM) response to mechanical stretching in vitro. Bronchial rings were sham (control) or passively sensitized overnight by using sera from donors demonstrating sensitivity to Dermatophagoides farinae and having immunoglobulin E (IgE) concentrations of 2,600 +/- 200 U/ml. Tissues were fixed isometrically to force transducers to measure responses to electrical field stimulation (EFS) and quick stretch (QS). The myogenic response to QS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 11 publications
(21 reference statements)
2
38
0
Order By: Relevance
“…Airway smooth muscle from these individuals with asthma and from sensitized dogs concomitantly demonstrated increased shortening velocity and capacity (17,18). Furthermore, seventh-generation human bronchi passively sensitized using human sera with high titers to house dust mite antigen showed, in addition to increased shortening velocity and capacity (19), robust myogenic responsiveness to quick stretch compared with sham-sensitized control airways (20). These in vitro findings paralleled the increased airway sensitivity and responsiveness observed in individuals with asthma.…”
Section: Mechanistic Explanations From In Vitro Studiessupporting
confidence: 52%
See 1 more Smart Citation
“…Airway smooth muscle from these individuals with asthma and from sensitized dogs concomitantly demonstrated increased shortening velocity and capacity (17,18). Furthermore, seventh-generation human bronchi passively sensitized using human sera with high titers to house dust mite antigen showed, in addition to increased shortening velocity and capacity (19), robust myogenic responsiveness to quick stretch compared with sham-sensitized control airways (20). These in vitro findings paralleled the increased airway sensitivity and responsiveness observed in individuals with asthma.…”
Section: Mechanistic Explanations From In Vitro Studiessupporting
confidence: 52%
“…We also found that the phosphorylation level of the regulatory myosin light chain 20 (rMLC 20 ) was not different between control and latrunculin B-treated tissues that had been flash-frozen near the end of the 20-minute oscillation protocol (1). These data indicated that the increased FFIR in the presence of latrunculin B could not be accounted for by a reduction of crossbridge activation in these TSM preparations.…”
Section: Actin Filament Length As a Regulator Of Ffirmentioning
confidence: 67%
“…More significantly, the force-generating ability of ASM is potentiated by stretch in infant guinea pigs but not in adult animals [215], and appears to be related to maturational changes in the release of prostanoids [216]. These findings may have relevance to the observations of WEIST et al [206], who showed that airway reactivity in healthy infants is not only greater than that in healthy adults, but is also insensitive to deep inspiration, similar to the situation in asthmatic adults [18] and in passively sensitised human bronchi [217]. Thus, there is reason to suspect that immature and asthmatic ASM may adapt differently to chronic length change.…”
Section: Effects Of Chronic Lung-volume Alteration and Smooth Muscle mentioning
confidence: 78%
“…In some asthmatic patients, a sustained bronchoconstriction may develop after taking one or more full inflations (13,18), an effect that has been attributed to a myogenic response triggered by the stretching of airway smooth muscle (22,23). In vitro, this behavior was observed after passive sensitization with allergic serum (14) or chemical agents able to convert airway smooth muscle from multiunit to single-unit conditions (23). In vivo, this phenomenon seems to occur only in a minority of subjects with rather severe asthma.…”
Section: Discussionmentioning
confidence: 99%